Thermostabilization and Thermosensitization of Herpesvirus - Wallis, Craig (1965)
Wallis, Craig (Baylor University College of Medicine, Houston, Tex.), and Joseph L. Melnick. Thermostabilization and thermosensitization of herpesvirus. J. Bacteriol. 90:1632–1637. 1965.—Herpesvirus, long considered as one of the most thermolabile of viruses, was stabilized by 1 m Na(2)SO(4) or Na(2)HPO(4) so that it withstood heating at 50 C, but the virus was not protected by 1 m MgCl(2), MgSO(4), or KH(2)PO(4), or 2 m KCl or NaCl; 1 m Na(2)SO(4) also stabilized herpesvirus at 25 and 37 C. In contrast, herpesvirus was made extremely thermosensitive in the presence of isotonic salt concentrations or of isotonic tris(hydroxymethyl)aminomethane buffer, especially at pH 7.2 or above. Partially purified virus was relatively thermostable when suspended in distilled water at pH 7.2, but in Earle's salt solution the virus immediately became thermosensitive. As found in tissue culture harvests, herpesvirus was thermolabile, but the virus was rendered stable at 50 C by simple dilution in distilled water. Protection by proteins or amino acids, generally accepted as virus-stabilizing agents, did not seem to be the result of a direct effect upon herpesvirus. The present data suggest that the added proteins counteract in part thermosensitizing effects of the salts contained in the virus harvest.